Sounding Fragilities: An Anthology - Lehmann, Irene; Palme, Pia (Hofheim Wolke, 2022)
Sounding Fragilities enacts a polyphony of writing on contemporary composition, music and performing arts in relation to music theatre. Co-edited by a theatre and performance scholar and by a composer and artistic researcher, this anthology considers its field of investigation through the lens of positionalities. Irene Lehmann and Pia Palme invite readers into intimate encounters with an artist’s practice, feminist and queer perspectives, and personal explorations into aspects of musicology, theatre studies, technology and ecology. By presenting female* composers who write with/through/about their own practice, Sounding Fragilities is a remarkable contribution to an interdisciplinary debate around the agency of artistic research. With this synthesis, the editors evaluate how moving beyond the binary of art and science reveals the rich yet fragile territories of artistic knowledge-production and literacy in music theatre.
Keywords: Music theater; Contemporary music; Composing; Performance; Feminism; Ecology